2019
DOI: 10.1186/s12866-019-1438-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of flow cytometry based adherence assay for Neisseria gonorrhoeae using 5′-carboxyfluorosceinsuccidyl ester

Abstract: BackgroundNeisseria gonorrhoeae is an obligate human pathogen and its adherence to host cells is essential for its pathogenesis. Gonococcal adherence assays are based on the enumeration of bacteria attached to human cells on solid media. Because conventional adherence assays are based on bacterial counts, they are often time consuming to perform and prone to observer bias. A flow cytometry based method, using the cell-permeable fluorescent dye 5′-carboxyfluoroscein succidyl ester (CFSE), was developed to drama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Flow cytometry-based adherence assay. Flow cytometric analysis of bacterial adhesion was performed as previously described 72 . Briefly, E. coli cultures were stained with CFSE (Cell-Trace CFSE Cell Proliferation Kit, Thermofisher, C34554) before infection of HCT116 and HT-29 cells at MOI 100, spun down for 4 min 300 x g to synchronize adhesion and incubated at 37°C, 5% CO2 for 3h.…”
Section: Isolation Ofmentioning
confidence: 99%
“…Flow cytometry-based adherence assay. Flow cytometric analysis of bacterial adhesion was performed as previously described 72 . Briefly, E. coli cultures were stained with CFSE (Cell-Trace CFSE Cell Proliferation Kit, Thermofisher, C34554) before infection of HCT116 and HT-29 cells at MOI 100, spun down for 4 min 300 x g to synchronize adhesion and incubated at 37°C, 5% CO2 for 3h.…”
Section: Isolation Ofmentioning
confidence: 99%
“…To adhere to cells, bacteria use a range of factors, from pili, fimbria, flagella, and other adhesins ( 62 64 ). Conventional adherence assays are laborious and based on counting bacteria on agar plates or from stained cells ( 28 , 65 ). Genetic methods, such as multi-plex PCR, test for the presence of multiple adhesin genes in a single reaction but do not provide evidence of functionality ( 29 ).…”
Section: Adhesion and Invasionmentioning
confidence: 99%
“…Breeuwer, Drocourt, Rombouts, and Abee (1994) and Breeuwer et al (1995) showed that FDA and carboxyfluorescein diacetate (CFDA) penetrated yeast rapidly but that esterase activity was limiting and an energy-dependent efflux of carboxyfluorescein from viable cells also impacted negatively on the efficacy of the staining method. Success has been reported with 5 -carboxyfluoroscein succidyl ester (CFDA-SE) with Neisseria gonorrhoeae (Thakur, Obradovic, Dillon, Ng, & Wilson, 2019).…”
Section: Metabolic Activitymentioning
confidence: 99%